2009
DOI: 10.1007/s11832-008-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications with flexible nailing of femur fractures more than double with child obesity and weight >50 kg

Abstract: Background Previous studies report that children above the 95th percentile in weight for their age had an increased risk for complications following titanium elastic nailing for femur fractures. The purpose of this study is to examine whether obesity, defined as body mass index (BMI) [ 95th percentile, and/or simple weight correlates with an increased rate of complications. Methods The incidence of complications was compared between obese and non-obese patients and also between patients who weighed C50 kg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 14 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…8 This retrospective study of 71 patients found a 46% complication rate (6/13) in obese children as compared with 17% (10/58) in those who were not obese. Garner and colleagues found a similar rate of complications in their retrospective weightmatched cohort study of children >47 kg undergoing operative fixation for a femur fracture with either titanium elastic nails or rigid trochanteric locked intramedullary nails.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…8 This retrospective study of 71 patients found a 46% complication rate (6/13) in obese children as compared with 17% (10/58) in those who were not obese. Garner and colleagues found a similar rate of complications in their retrospective weightmatched cohort study of children >47 kg undergoing operative fixation for a femur fracture with either titanium elastic nails or rigid trochanteric locked intramedullary nails.…”
Section: Discussionmentioning
confidence: 87%
“…[4][5][6][7] In pediatric orthopaedics, the literature has mostly been limited to studies examining the impact of weight and obesity on treatment of lower-extremity fractures, predominantly those involving the femur. [7][8][9] The results of these studies have not consistently demonstrated the effects of obesity on outcome.…”
mentioning
confidence: 99%
“…Titanium elastic nailing in this population had 6 of 15 incidence of complications, slightly less than the 46% to 50% noted in earlier studies. 13,14,16 This can be compared with 10 of 15 in the RLN cohort (P=0.17). Further analysis showed that, although not managed to reach statistical significance, the titanium elastic nails had a higher rate of malunion ( This study has several weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…This is a result of a number of factors, including the number of heavier children treated with TEN being limited because of current trends in fracture management, and the fact that we lost additional cases because of the weightmatching process. For these reasons, we chose a cutoff of 47 kg, not the 50 kg recommended by other investigators, 13,16 to allow for the inclusion of 2 additional matched groups (4 patients total). Considering our small numbers, we believe that the inclusion of these patients strengthens our data; further, only 1 of the 3 patients below 50 kg was treated with flexible intramedullary nailing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation